Digital Transformation in Public Services: Effect of RBA OSS Implementation in South Jakarta - Fitri Yunianto Hapsari; Dwi Putranto Riau; Sofjan Aripin (Jurnal Indonesia Sosial Teknologi, 2024)
This research investigates the effect of implementing the Risk-based Online Single Submission System (OSS RBA) on the quality of licensing services in South Jakarta. This research aims to evaluate policy implementation factors that influence the quality of licensing services and identify the implications of these findings. The research method used is Structural Equation Modeling (SEM) Partial Least Squares (PLS), with a population of business actors in South Jakarta and a sample of 100 respondents using the OSS RBA System. The results of the analysis show that the factors of Communication, Resources, Disposition, and Bureaucratic Structure positively and significantly influence the quality of licensing services. Even though the Public Factor does not show a statistically significant influence, its contribution still has an overall effect on service quality. These findings imply that greater attention should be paid to these aspects in designing policies and strategies to improve the effectiveness of public services. Thus, this research provides valuable insights for the development of practices and policies in digital technology-based public services.